Nursing process based on Betty Neuman's systemic model: A case study - Malihe Kabusi; Khadijeh Yazdi (Journal of Nursing Advances in Clinical Sciences)
This study aims to apply Betty Neuman's systemic model in the execution of the nursing process for a patient undergoing Whipple surgery. In this case study, a patient was assessed utilizing Neuman's model, wherein intrapersonal stressors encompassing physiological, psychological, socio-cultural, and spiritual dimensions, alongside interpersonal and extra personal stress factors, were systematically observed. Subsequent to the examination, three nursing diagnoses are delineated, adhering to the categorization stipulated by the International Association of Nursing Diagnosis of North America. Nursing care strategies are formulated based on three levels of prevention (primary, secondary, tertiary), as deemed significant within the framework of Neuman's perspective. The outcomes derived from this assessment informed the classification of nursing interventions and contributed to the categorization and evaluation of nursing outcomes. Consequently, it is advisable to consider the application of Neuman's model, along with other pertinent models, in the context of nursing care for the optimal well-being of patients/clients.